(untitled) (Journal of Universal Science Research, 2025)
Personal image plays a significant role in shaping social interactions, and the ways in which it is portrayed can differ across cultures. This study compares how personal image is constructed and communicated through language in the English and Uzbek phrasospheres. The research uses the IMRAD (Introduction, Methods, Results, and Discussion) method to explore how various linguistic expressions and phrases shape perceptions of personal identity in both cultures. Through qualitative analysis of interviews and a review of commonly used phrases, this study finds that while English emphasizes individualism, self-expression, and outward appearance, the Uzbek phrasosphere highlights respect, social harmony, and collective identity. The study offers valuable insights into how language reflects cultural values, offering practical implications for cross-cultural communication.